Contribuição metodológica aos estudos de degradação ambiental em bacias hidrográficas da região semiárida brasileira - Queiroz, Alexsandra Fernandes de (Universidade Federal Rural do Semi-Árido, 2017)
Today, there is a tendency of environmental studies using the watershed as a research unit, taking into account that it has the advantage of integrating various environmental aspects, as well as social and economic. In this context, there is a diversity of methodologies that aim to perform the characterization and environmental status of catchment areas, with the aim of guiding the forms of use and occupation thereof. Considering these assumptions, the present research aimed to accomplish a Physical-Conservationist Diagnosis (FCD) to determine the environmental degradation potential in the subwatershed of Pau dos Ferros/RN, through a multi-criteria analysis and the use of free geospatial tools. The methodology was based on an adaptation of the FCD by multi-criteria analysis with the support of GeoTechnologies, as image of remote sensing (Landsat 8 Satellite) and free software OF Geographical Information System (GIS) as the QGIS 2.14 and the SPRING 5.5. In the process of analysis, it was used four factors: slope, soils classes, soil vegetation cover classes and erosivity. For each factor, it was assigned different classes and the weights were defined by means of weighting of importance of each factor using the AHP (Analytic Hierarchical Process) to define the contribution and potential natural degradation of the area. In the aggregation of the four factors, Weighted Linear Combination was used, which resulted in the production of the map with the classes distribution to the potential natural degradation of the area. It has been found through the results, that among the factors evaluated what else contributed to the final map of the FCD, which represents the soil classes natural degradation potential of the area was slope, with 52.9%, followed by the soil classes factor with 31.5%, soil vegetation cover, with 10.5% and erosivity with 5.1%. It was noted that the potential classes to the environmental natural degradation in the subwatershed of Pau dos Ferros/RN ranged mostly from very weak to moderate. The multi-criteria analysis was efficient and consisted in an important tool in mapping the area of study and the FCD made possible an overview of the natural degradation condition of the study area
Keywords: Diagnóstico ambiental; Recursos naturais; Análise multicritério; Geoprocessamento; Environmental diagnostics; Natural resources; Multi-criteria analysis; Geoprocessing; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO